Morphological, Thermal, Physicomechanical and Optical Properties of Crosslinked Poly (Ester-Urethane-Acrylate): Effect of Added Methyl Methacrylate - Shyam Dev Maurya; Sanjay K. Nayak (Sustainable Chemical Engineering, 2024)
Poly (ester-urethane-acrylate) (PEUA) macromonomer was prepared by reacting two moles of isophorone diisocyanate (IPDI) with one mole of bis (1,4-butanediol ortho-phthalate) (BPE), followed by end-capping with two moles of 2-hydroxyethyl methacrylate (HEMA) in the presence of a dibutyltin dilaurate (DBTDL) catalyst. Thereafter, different ratios of methyl methacrylate (MMA) were added to the PEUA macromonomer to prepare crosslinked PEUA/MMA sheets. Fourier transform infrared spectrometry (FTIR), ultraviolet-visible spectrophotometry (UV-vis), and differential scanning calorimetry (DSC) techniques were employed to investigate the structure, optical transparency, and thermal properties of the crosslinked sheets. The effect of MMA on the polymerization shrinkage and abrasive wear properties of PEUA and their copolymers was also studied. The polymerization shrinkage study showed that the PEUA copolymer containing 40 wt% MMA had a more rigid microstructure with improved volume shrinkage and abrasive wear properties as compared with the other compositions of PEUA copolymers with MMA loadings of 80, 60, and 20%. The improvement was attributed to the better miscibility and compatibility of 40 wt% MMA with PEUA, as revealed by DSC, heat deflection temperature (HDT), and scanning electron microscope (SEM) studies.